Training For Maitreya Buddhism In Maitreya Buddhists at The Maitreya Holy Earth Pusdicate, Pekanbaru - Jelita, Rida; Irawati, Irawati; Sonika, Sonika; Saputra, Wawan; Steffanus, Jordy; Anton, Anton (Devotion : Journal of Research and Community Service, 2023)
A vegetarian consumption pattern or reducing consumption of animal meat will become a lifestyle for many people around the world during and after successfully passing the Global Covid19 Pandemic. During the Covid-19 Pandemic, although there has been no research on vegetarian food consumption patterns for the prevention of Covid-19, the impact on body stamina and the immune system has proven to be very significant. The purpose of this community service activity is to improve the skills of Maitreya Buddhists at the Pekanbaru Holy Earth Education and Training Center in making vegetarian meat. Activities are carried out using the training method, which includes discussion, education, practice, and mentoring. This type of artificial vegetarian meat produced is made from gluten. The resulting vegetarian-made meat products have aroma, texture, and tastes very true to the original, and free of cholesterol and germs that are usually carried in animal flesh. This community service activity is very beneficial for the target audience because it can open up vegetarian culinary business opportunities, including during the Covid-19 pandemic